KEKERABATAN BAHASA MELAYU BETAWI DI DESA KEDUNG JAYA KECAMATAN BABELAN KABUPATEN BEKASI DAN BAHASA JAWA DI DESA SALEBU KECAMATAN MAJENANG KABUPATEN CILACAP - Siti Robiah Majidah; Agustina Agustina (Faculty of Languages and Arts, Universitas Negeri Padang, 2019)
The purpose of this study was to determine the percentage of kinship level, determining the separation time, and explains the sound correspondence between Betawi Malay in Kedung Jaya Village, Babelan District, Bekasi Regency and Javanese in Salebu Village, Majenang District, Cilacap Regency. This kind of research is quantitative and qualitative research in the field of Comparative Historical studies. Based on the discussion of the results of data analysis, three research conclusions were obtained. First, the percentage of kinship level is 31%, with 155 relatives and 345 unrelated vocabularies. Second, the separation period of the two languages was 2,698 years ago. Third, the sound correspondence between the two languages can be seen in the form of 117 pairs of identical vocabularies, one phoneme of a total of 4 vocabularies, a compression of 4 vocabularies, a substitution of 23 vocabularies, a haplology of 1 vocabulary, afferasis of 3 vocabularies, and split a total of 3 vocabulary words. Thus, it can be concluded that based on the percentage of kinship level and the length of time the two languages are separated are included in the classification of stock.